Panorama 'Nationals' On Today - Unknown (Sunday Express)
Panorama national preliminaries begins and the results of the South Panorama semi-finals have been announced. The order of appearance of the bands are mentioned.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago